The cognitive poetics of horror fiction - Stewart-Shaw, Lizzie (2017)
This thesis explores the emotional experience of reading horror fiction from a cognitive-poetic perspective. The approach adopted in this thesis combines thorough consideration of Text World Theory, attention and resonance, emotion studies, and online reader responses to provide a detailed analysis of the texture of the horror-reading experience. Three classic contemporary horror novels are the analytical focus of this investigation: Ira Levin’s (1967) Rosemary’s Baby, Stephen King’s (1986) IT, and William Peter Blatty’s (1971) The Exorcist. These popular novels were chosen for their ability to evoke anxiety, fear, and disgust in readers, respectively. The primary intention of this thesis is to be an original contribution to the fields of stylistics, cognitive poetics, and the literary critical understanding of horror fiction. This thesis argues for a multifaceted approach to understanding the emotional experience of horror fiction, which is considered in terms of movement. As the conceptual metaphor EMOTION IS MOVEMENT recurs as an experiential effect of the horror-reading process throughout the reader-response data in this thesis, the frameworks applied aim to give insight to the readerly experience of conceptual movement. This thesis proposes that negation and other negatively oriented lexis establish the macabre ambience of the text-world space and that manipulation of movement through world-switching contributes to negative emotions evoked through the experience of these horror text-worlds.